Labor Market Power in Developing Countries: Evidence from Colombian Plants - Francesco Amodio; Nicolás de Roux (Institute of Labor Economics (IZA), 2021)
How much can employers in low and middle-income countries suppress wages below marginal productivity? Using plant and customs data from Colombia, we exploit pre- determined variation across plants in sales export destination combined with variation in exchange rates to generate plant-specific shocks to marginal revenue productivity and labor demand. We estimate a firm-level labor supply elasticity of around 2.5, implying that workers produce about 40% more than their wage level. Our results indicate that Colombian and US manufacturers have a comparable degree of labor market power.
Keywords: J42; L10; O14; O54; 330; labor market power; export; Colombia